Protecting Data on Smartphones and Tablets from Memory Attacks - Colp, Patrick; Zhang, Jianwen; Gleeson, James; Suneja, Sahil; Lara, Eyal de; Raj, Himanshu; Saroiu, Stefan; Wolman, Alec (ASPLOS '15 Proceedings of the Twentieth International Conference on Architectural Support for Programming Languages and Operating Systems, 2015)
Smartphones and tablets are easily lost or stolen. This makes them susceptible to an inexpensive class of memory attacks, such as cold-boot attacks, using a bus monitor to observe the memory bus, and DMA attacks. This paper describes Sentry, a system that allows applications and OS components to store their code and data on the System-on-Chip (SoC) rather than in DRAM. We use ARM-specific mechanisms originally designed for embedded systems, but still present in today's mobile devices, to protect applications and OS subsystems from memory attacks.